Hacia una visión integradora del concepto de empresario basado en competencias - Edmary Sinaí, Carrasco (REVISTA CIENTIFICA GLOBAL NEGOTIUM, 2022)
The organizations are in constant change and transformations as a result of the social, ecological and health dynamics that are experienced. This makes some concepts obsolete or too limited to respond to the necessary demands that exist in a digital economy. The purpose of this article is to reveal and argue the importance of a concept of entrepreneur with an integrative vision based on competencies. For this purpose, a theoretical-documentary review is carried out and analysis and logical reasoning are used, a concept of an entrepreneur is found based on 12 necessary skills for superior performance called an entrepreneur with purpose. It is concluded that the term "purpose" represents the will and awareness of the entrepreneur to achieve superior performance motivated by the search for balance throughout their business activity.
Keywords: Entrepreneur; Businessman; Entrepreneurship; Entrepreneur with purpose